Comparative effectiveness of induction chemotherapy for oropharyngeal squamous cell carcinoma: A population-based analysis. (March 2016) - Sher, David J.; Schwartz, David L.; Nedzi, Lucien; Khan, Saad; Hughes, Randall; Fidler, Mary Jo; Koshy, Matthew
Highlights: We used the National Cancer Database to compare the effectiveness of definitive chemoradiotherapy versus induction chemotherapy for patients with oropharyngeal squamous cell carcinoma. There was no difference in survival between these two strategies. Induction chemotherapy was associated with a nearly significant survival detriment in patients with human papillomavirus (HPV)-positive disease, but it led to significantly improved survival in individuals with high-risk (i.e. T4/N3) HPV-negative cancer. This analysis supports definitive chemoradiotherapy as the standard-of-care, but further research should be performed on induction chemotherapy in poor-prognosis cohorts. Summary: Objectives: Despite several randomized trials, the optimal chemotherapy paradigm for locally advanced oropharyngeal carcinoma (OPSCC) is controversial. This population-based analysis assessed the overall survival (OS) benefit of induction chemotherapy (IC) for patients with stage III–IVB OPSCC. Materials and Methods: Patients in the National Cancer Database with stage III–IVA-B OPSCC treated with curative-dose radiotherapy and IC or concurrent chemotherapy (CRT) between 2003 and 2011 were eligible. The primary outcome was OS, and secondary endpoints included OS for high-risk (T4 and/or N3 disease) and human papillomavirus (HPV) subsets. Results: Of the 14, 856 analyzed patients, 78% and 22% received CRT and IC, respectively. With a median follow-up for surviving patients of 44 months, the 5-year OS probability for the entire cohort was 66% (66% CRT vs. 64% IC, p  = 0.022). Multivariable survival analysis showed no significant difference between CRT and IC (hazard ratio, HR, 0.95 for IC, p  = 0.255), and sensitivity analyses to adjust for immortal time bias brought the HR to 1.0 ( p  = 0.859). There was also no OS difference for high-risk patients. There was a trend in favor of CRT for HPV-positive OPSCC (HR 1.63 with IC, p  = 0.064), with a significant OS benefit for HPV-negative, high-risk OPSCC (HR 0.63, p  = 0.048). Conclusion: For the vast majority of patients, including HPV-positive individuals, there was no difference in OS with IC, arguing for CRT to remain as the standard therapy. Subset analysis revealed a small cohort of aggressive cancer (T4/N3 HPV-negative) which may benefit from from IC, although selection bias could not be ruled out.